ANALYSIS OF THE SUITABILITY OF PHYSICS LABORATORY FACILITIES AND INFRASTRUCTURE - Muhammad Ridwan Azizi; Ratnawulan Ratnawulan (Physics Learning and Education, 2023)
This study aims to determine the level of suitability of physics laboratory facilities and infrastructure based on the Ministry of National Education Number 24 of 2007. The method in this research is descriptive quantitative using survey method. Data collection techniques using observation sheets have been adapted to Ministry of National Education Number 24 of 2007 and interviews. The subjects in this study were the facilities and infrastructure of the physics laboratory. The data analysis technique was carried out to describe the results of observations and interviews that had been carried out. Data analysis that will be carried out in the research is after the data is collected, the next step is to compare the existing physics laboratory facilities and infrastructure with Permendiknas Number 24 of 2007 whether they are suitability or not. The results of the research on the analysis of the suitability of the physics laboratory facilities and infrastructure at senio high school in west sumatera showed the level of conformity based on Ministry of National Education Number 24 of 2007 showed different results for each suggestion and infrastructure studied, namely in the learning facilities section of 100%, the basic measuring instrument of 84 .4%, practicum materials with a percentage of 92.4%, experimental tools by 69.2%, for educational media and other equipment and infrastructure with a percentage of 100%. Meanwhile, the results of the suitability of all existing facilities and infrastructure are 90% with the very appropriate category.